Aspectos da geometria neutra - Silva, Adriane Renófio da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this work we study some aspects of Neutral Geometry, so called because it is not assumed the Axiom of Parallels. We present results which are possible to be demonstrated assuming some axioms Incidence, Betweenness, Congruence and Measure are developed. We demonstrate the Saccheri-Legendre theorem and show that this geometry can not guarantee the existence of rectangles. We are not interested to construct an axiomatic theory, in the strict sense of the word

Neste trabalho estudamos alguns aspectos da Geometria Neutra, assim chamada porque não é assumido o Axioma das Paralelas. São apresentados resultados possíveis de serem demonstrados assumindo alguns Axiomas de Incidência, Ordem, Congruência e Medida. Demonstramos o Teorema de Saccheri-Legendre e mostramos que nesta geometria não se pode garantir a existência de retângulos. Não nos preocupamos em construir uma teoria axiomática, no sentido exato da palavra
Keywords: Euclides; Geometria; Geometria não-euclidiana; Geometry